Moral Development to Improve Students’ Discipline in Class V at MI AlHidayah Makassar - Nurlaelah, Nurlaelah; Subaedah, Subaedah (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The moral development of each learner should be the most important thing in the educational process in order to create real educational goals. Therefore, this study aims to describe the forms of moral development and obstacles in the implementation of learning in order to improve student discipline. The research method used is descriptive qualitative which focuses on the form of moral development and the constraints experienced in order to improve discipline. The subject was a class V MI AlHidayah Makassar. The data collection technique used was observation of the learning process, documentation and interviews with Islamic Religious Education (PAI) teachers, Madrasah heads, and several students at random. The data analysis used is descriptive qualitative with a nominal approach. The results obtained indicate that there are several forms of coaching carried out by teachers and other school managers, namely; direction, exemplary, coaching, punishment and reward. Each of these coaching patterns certainly has a positive impact, namely it can minimize the occurrence of indiscipline in students. Obstacles faced by teachers in improving discipline are limited collaboration with parents, guardians of students and environmental influences.